2021
DOI: 10.1155/2021/5560581
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Poses in Ballet in the Case of a Retired Classical Ballerina after Bilateral THA: A Case Report and Review of Literature

Abstract: Background. Ballet dance involves extreme range of motion (ROM) in the hip joint. This ROM can cause injuries including labral strain, tears, and subluxation episodes. Case Presentation. A 69-year-old female classical ballet dance instructor presented bilateral hip pain. The plain radiograph showed end-stage osteoarthritic change in the bilateral hip. She could neither dance nor perform daily activities. Bilateral hybrid total hip arthroplasty (THA) was performed. After surgery, she was able to demonstrate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This study is the first to report clinical and functional outcomes after THA in young, active, professional ballet dancers who intended to resume ballet after the surgery. Previous published studies 10–13 on THA in dancers report outcomes in patients who have either retired or who dance for leisure, mainly nonballet. This is most likely due to the low number of THAs performed on professional ballet dancers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study is the first to report clinical and functional outcomes after THA in young, active, professional ballet dancers who intended to resume ballet after the surgery. Previous published studies 10–13 on THA in dancers report outcomes in patients who have either retired or who dance for leisure, mainly nonballet. This is most likely due to the low number of THAs performed on professional ballet dancers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous published studies [10][11][12][13] on THA in dancers report outcomes in patients who have either retired or who dance for leisure, mainly nonballet. This is most likely due to the low number of THAs performed on professional ballet dancers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mizoguchi et al 14 reported on an experienced jazz dance instructor who underwent simultaneous bilateral THA using a transtrochanteric approach and the tailored postoperative physical therapy program that she followed. Morio et al 15 reported on a retired professional ballet dancer who underwent bilateral THA and was able to regain most of her prearthritic ROM, being able to perform the split position.…”
mentioning
confidence: 99%